The framework for regional collaboration in animal agriculture: The SADC animal agriculture network (SAARNET) - Lebbie, S.H.B. (Bunda College of Agriculture, 2001)
SACCAR's strategy emphasises that dynamic, productive and responsive agricultural research systems are essential to realising the food security potential of the Southern African Development Community (SADC) region and the continuous development of technologies for different sectors of agriculture will depend on a co-ordinated effort by countries of the SADC region. It is against this backdrop that SACCAR has adopted networking as a strategy to achieve strong co-ordination and collaboration among SADC member states for regional development and advancement in agriculture. The SADC Animal Agriculture Research Network (SAARNET) was therefore formed in 1997 as a joint effort between SACCAR and International Livestock Research Institute (ILRI) to provide the framework for regional co-ordination and collaboration in animal agriculture. SAARNET as a regional network aims at promoting partnerships between different stakeholders (institutes, governments, donors, farmers and research disciplines) to solve common problems. Partnerships will be strengthened between stakeholders through participatory approaches (workshops, seminars, field days and training sessions) to plan and prioritise activities, and share information, technology, and materials. The organisation and operation of a collaborative research network such as SAARNET is very challenging though rewarding. It is therefore critical that the institutional framework and activities of the research network are clearly related to the needs and goals of all its stakeholders, including the farmer. Also crucial to the success of the network are simple but efficient mechanisms for co-ordination, information dissemination, monitoring and evaluation, and impact assessment. Above all, a network needs sustainable funding to be able to implement its programmes and ensure the effective participation of the stakeholders, particularly the National Agricultural Research Institutions (NARIs). This paper elaborates SAARNETS strategy to achieve this daunting task.